PENGARUH BUDAYA ORGANISASI, EFEKTIVITAS KEPEMIMPINAN DAN STRES KERJA TERHADAP KINERJA - Suherman Suherman (Universitas Negeri Jakarta, 2011)
The purpose of this research is to find out the effect of organization culture, leadership effectiveness, and job stress on the performance of Junior High School Principals in Murung Raya Regency, Central Kalimantan Province. This research is a causal study using path analysis on the 74 population (Principals) of Junior High School. There were 63 persons (Principals) of analysis unit used as the sample whom are chosen randomly. There are five results of this research, among others: 1). there is a positive direct influence of organization culture on job stress, 2). there is a positive direct influence of organization culture on performance, 3). there is a positive direct effect of job stress on leadership effectiveness, 4). there is a positive direct effect of leadership effectiveness influence on the performance and 5). there is a positive direct effect of job stress on performance. Therefore, a good performance of Junior High School Principals may be increased further by boosting the efforts of human resources especially in the success of local government program in Murung Raya Regency such as to become healthy and smart in 2013. Besides, apart from that, other variables also must be considered for the next research.